Transcriptomic and Hormonal Analyses Reveal that YUC-Mediated Auxin Biogenesis Is Involved in Shoot Regeneration from Rhizome in Cymbidium - Liu, Yang; Zhang, Hai-Liang; Guo, He-Rong; Xie, Li; Zeng, Rui-Zhen; Zhang, Xiang-Qian; Zhang, Zhi-Sheng (Frontiers in Plant Science, 2017)
Cymbidium, one of the most important orchid genera in horticulture, can be classified into epiphytic and terrestrial species. Generally, epiphytic Cymbidium seedlings can be easily propagated by tissue culture, but terrestrial seedlings are difficult to propagate. To date, the molecular mechanisms underlying the differences in the ease with which terrestrial and epiphytic cymbidiums can be propagated are largely unknown. Using RNA-sequencing, quantitative reverse transcription PCR and enzyme-linked immunosorbent assay (ELISA), Cymbidium ‘Xiaofeng’ (CXF), which can be efficiently micropropagated, and terrestrial Cymbidium sinense ‘Qijianbaimo’ (CSQ), which has a low regeneration ability, were used to explore the molecular mechanisms underlying the micropropagation ability of Cymbidium species. To this end, 447 million clean short reads were generated, and 31,264 annotated unigenes were obtained from 10 cDNA libraries. A total of 1,290 differentially expressed genes (DEGs) were identified between CXF and CSQ during shoot induction. GO (Gene Ontology) enrichment analysis indicated that the DEGs were significantly enriched in auxin pathway-related GO terms. Further analysis demonstrated that YUC and GH3 family genes, which play crucial roles in the regulation of auxin/IAA (indole-3-acetic acid) metabolism, acted quickly in response to shoot induction culture in vitro and were closely correlated with variation in shoot regeneration between CXF and CSQ. In addition, the study showed that IAA accumulated rapidly and significantly during shoot induction in CXF compared to that in CSQ; in contrast, no significant changes in other hormones were observed between CXF and CSQ. Furthermore, shoot regeneration in CXF was inhibited by a yucasin-auxin biosynthesis inhibitor, indicating that increased IAA level is required for high-frequency shoot regeneration in CXF. In conclusion, our study revealed that YUC-mediated auxin biogenesis is involved in shoot regeneration from rhizome in Cymbidium.